FACTORING CONTRACT IN LAW OF THE REPUBLIC OF SERBIA - Marković, Velisav I (Pravni zapisi, 2014)
Factoring contract in law of the Republic of Serbia is designated, formal, obligatory for both contract parties, burdening, commutative by its approach, with durable benefits and intuitu personae contract, whereby one contract party sells to other counterparty-factor existent but matured claim, or future short-term monetary claims against the debtor, resulting under the contract of sale of goods or services, and counterparty-factor undertakes to pay compensation to assignor. By the adoption of Law on factoring in 2013, factoring contract became a designated contract in Law of the Republic of Serbia. The author analyzes in detail the characteristics of the contract, the rights and obligations of the factors and the assignor, considering the provisions of Law on factoring and other regulations.